EARTH-MOON SYSTEM, PLANETARY SCIENCE, AND LESSONS LEARNED - Taylor S.R.; Pieters C.M.; MacPherson G.J. (My University, 2006)
The origin and evolution of the Moon is now well understood. Many bizarre theories were proposed to account for our satellite before these were swept away by the data from the Apollo missions. We now understand with the benefit of hindsight that we are looking at a very ancient object whose surface has changed little for the past 3.5 b.y.